2012
DOI: 10.1097/sla.0b013e31824336e2
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Stress Response and Postoperative Immune Function After Laparoscopy or Open Surgery With Fast Track or Standard Perioperative Care

Abstract: This randomized trial showed that immune function of HLA-DR in patients undergoing laparoscopic surgery with fast track care remains highest. This can be attributed to type of surgery and not aftercare. These results may indicate a reason for the accelerated recovery of patients treated laparoscopically within a fast track program as described in the LAparoscopy and/or FAst track multimodal management versus standard care (LAFA-Trial) (www.trialregister.nl, protocol NTR222).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
225
1
10

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 299 publications
(245 citation statements)
references
References 15 publications
8
225
1
10
Order By: Relevance
“…The LAFA study looked at four groups of surgical patients undergoing colorectal surgery: (1) open surgery within an ERP, (2) open surgery without an ERP, (3) laparoscopic surgery within an ERP, and (4) laparoscopic surgery without an ERP. 32 IL-6 and C-reactive protein levels were highest in the open surgery group, as expected. The biggest impact on improving postoperative immune function (measured by effect on HLA-DR) was having laparoscopic surgery and the addition of an ERP improved this further.…”
Section: Evidence Base For Enhanced Recovery Pathwayssupporting
confidence: 62%
“…The LAFA study looked at four groups of surgical patients undergoing colorectal surgery: (1) open surgery within an ERP, (2) open surgery without an ERP, (3) laparoscopic surgery within an ERP, and (4) laparoscopic surgery without an ERP. 32 IL-6 and C-reactive protein levels were highest in the open surgery group, as expected. The biggest impact on improving postoperative immune function (measured by effect on HLA-DR) was having laparoscopic surgery and the addition of an ERP improved this further.…”
Section: Evidence Base For Enhanced Recovery Pathwayssupporting
confidence: 62%
“…3,4 Also, cellular immune responses appear to be less affected by laparoscopic colorectal resection compared with open resection as determined by total lymphocyte count, CD4 þ and CD8 þ T cells, interferon-c, and human leukocyte antigen-DR. [5][6][7][8] However, these differences are not consistent at all time intervals, and further studies are needed to fully characterize the importance of temporal changes in these markers. Furthermore, despite potential benefits, laparoscopic surgery still remains technically challenging in rectal cancer and will not be suitable for all patients.…”
mentioning
confidence: 99%
“…IL-6 is used as postoperative complications and predictor of morbidity. Veenhof et al (12) reported that the patients who underwent laparoscopic surgery were affected positively at HLA-DR, CRP and IL-6 levels. Early recovery, early onset bowel motility, and short hospitalization may be associated with these effects in patients undergoing laparoscopic surgery.…”
Section: Discussionmentioning
confidence: 99%